2020
DOI: 10.1155/2020/3402178
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Description of Annual Temperature and Rainfall in the Bawku Area of Ghana

Abstract: With varied implications, Ghana’s temperature and rainfall are projected to rise and decline, respectively. A study exposing specific areas of concern for appropriate responses in this regard is a welcome one. This study sought to describe the temporal variations in temperature and rainfall in the Bawku Area of Ghana. A forty-year (1976–2015) daily climate data was collected on three meteorological stations from the Ghana Meteorological Agency. Normality test, homogeneity test, Standardised Precipitation Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…This trend was only significant in May at 5%. These findings are in agreement with that of Asamoah and Ansah-Mensah [36], who found a rising trend in the rainfall in northern Ghana. These results also corroborate that of Ezin et al [39], who observed similar trends for rainfall in northern Benin.…”
Section: Serial Correlation Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…This trend was only significant in May at 5%. These findings are in agreement with that of Asamoah and Ansah-Mensah [36], who found a rising trend in the rainfall in northern Ghana. These results also corroborate that of Ezin et al [39], who observed similar trends for rainfall in northern Benin.…”
Section: Serial Correlation Analysissupporting
confidence: 93%
“…The long-term average temperatures were 27.4, 26.7, 28.9 and 28.1 • C in Kara, Niamtougou, Mango and Dapaong, respectively. These values are similar to the ones reported by Asamoah and Ansah-Mensah [36] in northern Ghana. Figure 3 represents the time series annual rainfall in northern Togo.…”
Section: Serial Correlation Analysissupporting
confidence: 91%
“…The body temperature and body weight of two groups of nude mice were detected, and the changes of body temperature and body weight of the two groups of nude mice were recorded and compared before and after modeling, 1 week after modeling, 2 weeks after modeling, 3 weeks after modeling, and before sacrifice. The detection method of anal temperature referred to the research of Asamoah and Ansah-Mensah in 2020 [ 10 ]. Before testing, animals were allowed to empty their stools, and the anal temperature of all nude mice was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it is necessary for detailed statistical studies to be conducted with more emphasis on particular rainfall seasons. Aside from the rainfall trends and variations, many attempts have been made to understand different aspects of the climate system in Ghana which include the onset, cessation, and length of the rainfall seasons, rainfall and dry spell predictions, and temperature trend analysis [15][16][17][18][19]. Interestingly, the above studies have successfully explained the behaviors of temperatures, rainfall, dry spells at seasonal and sub-seasonal scales and their link to major meteorological parameters like seas surface temperatures (SST) and intertropical discontinuity.…”
Section: Introductionmentioning
confidence: 99%